La carte de végétation du CNRS à l'ère du numérique - Sophie Leguédois (Unité Mixte de Recherche 8504 Géographie-cités, 2011)
In this paper we present the digitalisation of the map of the vegetation of France edited by the CNRS in 64 sheets between 1947 and 1991. The geographical covers and the databases built during this work are gathered in a geographical database called “Base de Données Géographique de la VÉGétation de la France” (BDGveg_FR). The main covers show respectively the vegetation succession stages, as a georeferenced scan, at 1/200,000, and the harmonised map of the potential vegetation, in a vector format, at 1/1,000,000. The harmonised map of the potential vegetation is linked with a national 6-level typology synthesised from the keys of the 64 sheets. Possible uses of the BDGveg_FR are shown with some examples on the determination of the factors of vegetation distribution (altitude, geology, soil and climate) by intersecting it with others sources of geographical data (digital elevation model, vector covers at 1/1,000,000 of soil and geology). The BDGveg_FR is actually complementary to the other databases on the vegetation of France presently available thanks to its period of time, its local and national scales, its exhaustive cover and its information on the plant associations. It can be used to assess the impact of global changes (e.g. climate, atmospheric pollution) on ecosystems.